2021
DOI: 10.1007/s10067-021-05760-1
|View full text |Cite
|
Sign up to set email alerts
|

Expectancies as predictors of symptom improvement after antimicrobial therapy for persistent symptoms attributed to Lyme disease

Abstract: Introduction/Objective Expectancies about symptom improvement or deterioration are reliable predictors of symptom progression and treatment outcomes (symptom resolution or symptomatic improvement) in many (non-)pharmacological studies and treatments. This study examined predictors of symptom improvement after antimicrobial therapy for persistent symptoms attributed to Lyme disease, hypothesizing particularly pre-treatment expectancies regarding symptom improvement to be predictive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We did not include a questionnaire to assess patients' subjective cognitive problems in detail, nor did we ask them about their expectancy regarding the outcome when included in the acute phase. A recent study on expectancy regarding outcome showed that both premorbid function and positive expectancy were related to a more beneficial outcome in patients [46]. Patients reported higher level of fatigue compared with the controls, and patients on sick leave related to neuroborreliosis reported higher level of fatigue compared with patients not on sick leave.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We did not include a questionnaire to assess patients' subjective cognitive problems in detail, nor did we ask them about their expectancy regarding the outcome when included in the acute phase. A recent study on expectancy regarding outcome showed that both premorbid function and positive expectancy were related to a more beneficial outcome in patients [46]. Patients reported higher level of fatigue compared with the controls, and patients on sick leave related to neuroborreliosis reported higher level of fatigue compared with patients not on sick leave.…”
Section: Discussionmentioning
confidence: 98%
“…We did not include a questionnaire to assess patients’ subjective cognitive problems in detail, nor did we ask them about their expectancy regarding the outcome when included in the acute phase. A recent study on expectancy regarding outcome showed that both premorbid function and positive expectancy were related to a more beneficial outcome in patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain can be shaped by different types of expectancies [1,2]. Expectancies of upcoming pain (i.e., pain expectancies), as well as expectancy-related factors such as anxiety, catastrophizing, and optimism have been found to be associated with pain [1,[3][4][5]]. Yet, their combined role in shaping pain experiences in chronic pain conditions, such as fibromyalgia, is fairly unknown.…”
Section: Introductionmentioning
confidence: 99%